2017
DOI: 10.1177/0149206317690584
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Road Map of Entrepreneurial Equity Financing Research: Venture Capital, Corporate Venture Capital, Angel Investment, Crowdfunding, and Accelerators

Abstract: Equity financing in entrepreneurship primarily includes venture capital, corporate venture capital, angel investment, crowdfunding and accelerators. We take stock of venture financing research to date with two main objectives: a) to integrate, organize and assess the large and disparate literature on venture financing; and b) to identify key considerations relevant for the domain of venture financing moving forward. The net effect is that organizing and assessing existing research in venture financing will ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
319
1
24

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 397 publications
(354 citation statements)
references
References 241 publications
(347 reference statements)
10
319
1
24
Order By: Relevance
“…We build on a considerable legacy of work regarding entrepreneurial finance (Drover et al, 2017). A deliberate attempt has also been made to draw upon the research gaps identified in the nascent crowdfunding literature (see Bruton et al, 2015;Moritz and Block, 2016;Pichler and Tezza, 2016;Short et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We build on a considerable legacy of work regarding entrepreneurial finance (Drover et al, 2017). A deliberate attempt has also been made to draw upon the research gaps identified in the nascent crowdfunding literature (see Bruton et al, 2015;Moritz and Block, 2016;Pichler and Tezza, 2016;Short et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Signalling theory (Spence, 1974) has proven to be an impactful theoretical lens to understand how organizational outsiders, such as prospective consumers or equity investors, go about assessing the quality of a business (e.g., Certo, 2003;Drover et al, 2017;Miller and del Carmen Triana, 2009;Plummer et al, 2016;Reuer et al, 2012;Stuart et al, 1999). This perspective argues that because organizational quality cannot be directly observed, decision-makers must rely on information signals thought to correlate with quality (Bergh et al, 2014;Pollock et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, while authors enquire about the institutional causes that may lead to the development of VC, they confine their analysis to the comparison between the USA and Sweden, without enlarging their perspective and analysing evidence produced in other institutional contexts. Finally, the recent review performed by Drover et al (2017) looks, among other things, on how different (formal and informal) governance mechanisms impact the VC-entrepreneur relationship. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the recent review performed by Drover et al . () looks, among other things, on how different (formal and informal) governance mechanisms impact the VC‐entrepreneur relationship.…”
mentioning
confidence: 99%